Comparative analysis of traditional and UAV bridge inspections performed by New Mexico State University - Navarro-Montero, Valeria (2023)
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2023.